ANALISIS ADVERSE DRUG REACTIONS OBAT ANTI RETROVIRAL PADA PENGOBATAN PASIEN HIV/AIDS DI RSUD GUNUNG JATI CIREBON TAHUN 2013 - Nur Rahmi Hidayati; Syamsudin Abdillah; Sesilia A. Keban (Pharmaciana, 2016)
Acquired Immunodeficiency Syndrome (AIDS) is a disease caused by infection with Human Immunodeficiency Virus (HIV). The pharmacology treatment for the infection was antiretroviral therapy. The problem from the use of antiretroviral drugs (ARV) is the emergence of unwanted drug reactions (adverse drug reaction). The purpose of this study was to identify and analyze the incidence of adverse drug reactions from the use of antiretroviral drugs in the treatment of patients with HIV / AIDS that occurred in RSUD Gunung Jati Cirebon. This study involves 122 patients. Data were obtained from medical records and patient interview form. The data were evaluated with a descriptive analysis of demographic profile of patients and the percentage of adverse drug reaction (ADR) The results showed an adverse drug reaction (ADR) on the use of antiretroviral drugs in the treatment of patients with HIV / AIDS in RSUD Gunung Jati Cirebon. ARV regimens are the most widely used is the combination of Zidovudine + Lamivudine + Nevirapine / Efavirenz (AZT + 3TC + EFV) as much as 31.2% (38 people). Duration of therapy ARV in Seroja Clinic RSUD Gunung Jati Cirebon most is> 2 years - 4 years 28.7% (35 people). Types of adverse drug reaction (ADR), which occurs in the use of antiretroviral drugs in the treatment of patients with HIV / AIDS in RSUD Gunung Jati Cirebon include: headache (22.1%), fatigue (6.8%), anemia (9.3%), itching (14.4%), nausea / vomiting (20.1%), diarrhea (7.2%), lipodystrophy (2.0%), rash (11.3%), skin discoloration (1.6%), neuropathy (1.6%) and sleep disorders (3.6%).